Characterization of poly (lactic acid) composite reinforced with cellulose and keratin treated with 1-butyl-3-methylimidazolium chloride / Khaw Ying Ying - Khaw , Ying Ying (2019)
Biodegradable polymers such as poly(lactic acid) (PLA) were receiving much attention in the recent years due to the plastic pollution that filled up the ocean, causing harm to the marine biodiversity. Due to the relative high cost and poor mechanical properties of biodegradable polymers, microcrystalline cellulose (MCC) and keratin from chicken feather fibers (CFF) reinforcements were introduced in PLA to determine the effect of these fillers to the thermal, mechanical and morphological properties to the composites. Dissolution of fillers in ionic liquid (IL) of 1-butyl-3-methylimidazolium chloride (BMIMCl) were implemented to investigate its enhancement of CFF and MCC dispersion in PLA matrices. The PLA composites films were fabricated via measuring mixer and compression molding at 180 oC with 1 wt% of fillers consist of 5 compositions of CFF to MCC, namely 100/0, 70/30, 50/50, 30/70 and 0/100 respectively. High intensity of the composite absorption peaks in Fourier transform infrared spectra confirmed that the polymer blends were unaffected by the high temperature processing and ionic liquid (IL). As CFF/MCC ratio increased in the composites without IL, glass transition temperature, Tg decreased. The Tg further declined with BMIMCl added composites due to the chain flexibility increment and shortening of polymer chain length. This was in contrast to the increase in Vickers hardness and thermal stability as CFF composition increased in the presence of BMIMCl. Incorporation of BMIMCl in the composites produced porous structure in the PLA matrices as seen in scanning electron microscope (SEM) images which corresponded to their relative reduction in Tg, melting temperature (Tm) and thermal stability as compared to composites without IL. Apart from no phase separation observed in SEM, BMIMCl were able to enhance the composite compatibility by reducing double Tg to single Tg in 0/100 and 100/0 samples. Although PLA-CFF70MCC30IL obtained the highest crystallinity, χc of 46 % in differential scanning calorimetry (DSC), X-ray diffraction patterns showed that PLA-CFF70MCC30 was in turn to achieve the highest crystallinity index (CI) of 41 %. Despite the effect of BMIMCl to the composites were more significant than fillers compositions, 70/30 ratio was the best in attaining optimum compatibility and polymer chain flexibility.